Islamic Eco-Theology in the Age of Climate Crisis: A Critical Reading of Ali Jum‘ah’s Environmental Thought - Darlis, Darlis; Umar, Nasaruddin; Febriyani, Nur Arfiyah; Hariyadi, Muhammad; Arief, Ahmad (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2026)
Numerous studies have examined ecological ethics from an Islamic perspective; however, Ali Jum‘ah’s thought, particularly his contributions to an epistemological and spiritual framework of ecology, has not yet received sufficient critical attention in the academic literature. This research examines the ecological thought of Sheikh Ali Jum‘ah through content analysis of his book al-Bi’ah wa al-Ḥifẓ ‘Alayhā min Manẓūr al-Islāmī. The research argues that Ali Jum‘ah positions mahabbah (love) as the highest ethical form of the human–environment relationship, articulated through tajallī (divine manifestation in creation) and jamāliyyah (beauty as contemplative access). These concepts frame nature as a reflection of the asmā’ Allāh and foster an affective bond between humans and the cosmos. This research contributes by conceptualizing mahabbah as a substantive ecological ethic and by identifying a shift from a normative fiqh-oriented approach toward a Sufi-based framework of cosmic ethics as a foundation for ecological sustainability in Islam. الملخص تناولت دراساتٌ عديدة الأخلاقيات البيئية من منظور إسلامي، غير أنّ فكر علي جمعة—ولا سيما إسهاماته في بناء إطار بيئي ذي طابع معرفي وروحي—لم يحظَ بعدُ باهتمام نقدي كافٍ في الأدبيات الأكاديمية. تهدف هذه الدراسة إلى تحليل التصور البيئي للشيخ علي جمعة من خلال تحليل المحتوى لكتابه البيئة وحفظها من منظور إسلامي. وتُبيّن الدراسة أنّ علي جمعة يُؤسِّس علاقة الإنسان بالبيئة على مفهوم المحبّة بوصفها أعلى قيمة أخلاقية، وذلك من خلال مفهومي التجلّي والجماليّة بوصفهما مدخلين للتأمّل. وتُقدَّم الطبيعة في هذا الإطار باعتبارها مرآةً لأسماء الله الحسنى، بما يُنشئ رابطةً وجدانية وروحية بين الإنسان والكون. وتسهم هذه المقالة في بلورة مفهوم المحبّة بوصفه أخلاقًا بيئيةً جوهرية، وفي الكشف عن تحوّلٍ إبستمولوجي من مقاربة فقهية معيارية إلى إطار صوفي قيمي يقوم على أخلاقيات كونية تُشكّل أساسًا للاستدامة البيئية في الفكر الإسلامي. Abstrak Berbagai studi telah mengkaji etika ekologis dari perspektif Islam; namun pemikiran Ali Jum‘ah, khususnya kontribusinya dalam membangun kerangka ekologi yang bersifat epistemologis dan spiritual belum memperoleh perhatian kritis yang memadai dalam literatur akademik. Penelitian ini mengkaji pemikiran ekologis Syekh Ali Jum‘ah melalui analisis isi terhadap karyanya al-Bi’ah wa al-Ḥifẓ ‘Alayhā min Manẓūr al-Islāmī. Penelitian ini berargumen bahwa Ali Jum‘ah menempatkan mahabbah (cinta) sebagai bentuk etika tertinggi dalam relasi manusia–lingkungan, yang dirumuskan melalui konsep tajallī (manifestasi ilahi dalam ciptaan) dan jamāliyyah (keindahan sebagai jalan kontemplasi). Kedua konsep ini memandang alam sebagai refleksi dari asmā’ Allah serta menumbuhkan ikatan afektif antara manusia dan kosmos. Penelitian ini berkontribusi dengan mengonsepsikan mahabbah sebagai etika ekologis yang substantif serta mengidentifikasi pergeseran dari pendekatan normatif-legalistik (fiqh) menuju kerangka etika kosmik berbasis tasawuf sebagai landasan keberlanjutan ekologis dalam Islam.